THE ROLE OF @OFFICIALDARSUN IN CONSTRUCTING KH. ALI MUSTAFA YAQUB'S IDENTITY: Digital Da’wah Perspective - Sari Ratna Dewi; Andi Faisal Bakti (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
The research problem addresses shifts in religious communication within the digital era, where scholars' identities are shaped not only by direct interaction but also by curated representations on social media platforms. This study examines how the Instagram account @officialdarsun constructs the identity of KH. Previous research by Ali Mustafa Yaqub focused on content, production, and audience. The central argument is that the construction of ulama identity posthumously is influenced by message selection, presentation strategies, and the negotiation of meaning between account managers and the public. The theoretical and conceptual framework is informed by Branston and Stafford's work in The Media Student's Book (2003: 265–279), which highlights the importance of analyzing content, production, audience, and academic perspectives in media research. The methodology adopts a constructivist paradigm and an interdisciplinary approach, integrating communication science, digital media studies, and da'wah-hadith. The research employs virtual ethnography, utilizing non-participatory observation, digital documentation, interviews, uploaded recordings, archive review, and literature review. Data analysis involves reduction, visual reading, narrative interpretation, and presentation of findings, with validity ensured through source triangulation. The findings indicate that directed curation, production strategies, and audience engagement are crucial in affirming Kiai Ali's scholarly authority in digital spaces and demonstrate how religious identity can persist through media construction. This research offers a significant contribution to the field of Islamic communication in the context of the rapidly evolving digital era.